CSR and Sustainability Report for Nonprofit Organizations. An Italian Best Practice - GAZZOLA, Patrizia; RATTI, Massimo; AMELIO, Stefano (Management Dynamics in the Knowledge Economy, 2017)
The purpose of this paper is to analyze the sustainability report for the communication of Corporate Social Responsibility (CSR) in a nonprofit organization. To this aim, an Italian case study is analyzed: the Fondazione Renato Piatti Onlus, a nonprofit organization of Social Utility. In the first part, we analyze the CSR for nonprofit organizations and the sustainability report (also called ‘social balance’). In the second part, we present evidence from the case study. The research is exploratory in nature when considering the connection of corporate social responsibility efforts to the nonprofit sector, a qualitative methodology was chosen over quantitative methods. Specifically, the case study was used to show what strategy a nonprofit organization can develop. Nowadays CSR strategies received a growing attention from both businesses and nonprofit organizations but also from the EU which forced large public-interest entities to present a social balance. For nonprofit organizations, applying social responsibility is not a voluntary issue. Nonprofit organizations have an ethical obligation to their stakeholder and to the public to conduct their activities with accountability and transparency. Scholars have increasingly been studying the impact of corporate social responsibility as a business strategy in for-profit companies. However, there is still lack of researches on how nonprofit organizations implement CSR into the strategy. As a consequence of the above remarks, a large part of nonprofit organizations fails to correctly implement a successful long term CSR strategy. The Fondazione Renato Piatti Onlus belongs to that group that has been able to incorporate social responsibility within the organization, then expanding its content into a social report drawn up in accordance with the guidelines of the Italian Agency for the Third Sector.